EVALUATION OF DIFFERENT INTERCROPPING SYSTEM IN SUNFLOWER (Helianthus annuus L.) ANDMUNGBEAN (Vigna radiata L.) - Mowafaq Jubr Al-Layla; Waleed Shahadha Khalid Al-Juheishy (Mesopotamia Journal of Agriculture)
The experiment was carried out at Nineveh governorate. Two verities of Sunflower (Mungreen and Loess) and two verities of Mungbean (Greengram and Blackgram). were planted in five intercropping systems (one row Sunflower + one row Mungbean, two rows Sunflower + one row Mungbean, one row Sunflower + two rows Mungbean, two rows Sunflower + two rows Mungbean , and sole crop for sunflower and Mungbean).The experiment were by using Randomized Complete Block Design (R.C.B.D) with three replications. Testing the mean values of treatments by using: Duncan test and Dunnett test. The most important results can be summarized as follows: The treatment (one row Sunflower + two rows Mungbean) gave a higher values for most of the characteristics studied including (the head diameter, no. of seeds/head, weight of (1000) seeds, seed yield and biological yield in sunflower for both years. It was also observed that most of the intercropping systems gave a significant higher values then these planted as individual crops when using Dunnett test. The two treatments of sole Mungbean were superior in both years for both variety in all the investigated characteristics of the Mungbean yield except for the percentage of protein in the first year. and the sole Mungbean which were superior to intercropping when using Dunnett test.